2016
DOI: 10.1007/s13105-015-0460-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wortmannin on cardioprotection exerted by ischemic preconditioning in rat hearts subjected to ischemia-reperfusion

Abstract: Ischemic preconditioning (IPC) is one of the most powerful interventions to reduce ischemia-reperfusion injury. The aim of the present study was to investigate the involvement of the phosphatidylinositol-3-kinases (PI3Ks) family in cardioprotection exerted by IPC and the relationship between preservation of mitochondrial morphology and ATP synthesis capacity. In this regard, macroautophagy (autophagy) is considered a dynamic process involved in the replacement of aged or defective organelles under physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In this study, two additional groups of rats, namely the W+LEP group and W+LEP+EE group (LEP and LEP+EE models were treated with wortmannin, respectively) were used. Wortmannin has been reported to reduce the myocardial protective effects of ischemic conditioning by inhibiting autophagy [34]. In this study, the LC3-II levels were significantly decreased in the W+LEP and W+LEP+EE groups, thus suggesting that pretreatment with wortmannin might inhibit LEPand LEP+EE-induced formation of autophagosomes.…”
Section: Changes Of Ampk Mtor and Ulk1 Expression During Latementioning
confidence: 50%
“…In this study, two additional groups of rats, namely the W+LEP group and W+LEP+EE group (LEP and LEP+EE models were treated with wortmannin, respectively) were used. Wortmannin has been reported to reduce the myocardial protective effects of ischemic conditioning by inhibiting autophagy [34]. In this study, the LC3-II levels were significantly decreased in the W+LEP and W+LEP+EE groups, thus suggesting that pretreatment with wortmannin might inhibit LEPand LEP+EE-induced formation of autophagosomes.…”
Section: Changes Of Ampk Mtor and Ulk1 Expression During Latementioning
confidence: 50%
“…The W + EEP + EE group exhibited swelling, which was validated by an increase in the number of COX4/1-labeled mitochondria. Taken together, we demonstrated that the W + EEP + EE group had insufficient mitochondrial clearance compared to EEP + EE, which was possibly associated with wortmannin-induced inhibition of autophagy resulting in increased oxidative injury [ 11 ]. Therefore, EEP-induced cardioprotection does not affect the morphology of mitochondria, and mitophagy plays a role in protecting against EE-induced mitochondrial alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Acute cardiovascular stresses such as myocardial infarction (MI), ischemic reperfusion (I/R), or prolonged high-intensity exercise are strongly associated with a rapid increase in oxidative stress levels and morphological alterations in the mitochondria [ 5 11 ]. Therefore, oxidative stress acts as both inducer and reflector of mitochondrial dysfunction [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both EP and IP, the autophagy maintenance of ATP synthesis capacity is crucial to generating the adaptive promotion for additional cardiovascular stress. Such effects could be eliminated by PI3K inhibition, which is a possible mechanism to explain the suppression of ischemia-hypoxia in high-intensity exercise [12,37]. However, disruption between the autophagosome and lysosomes may reduce the efficiency of autophagy, resulting in interruption of the autophagic flux [38].…”
Section: Exercise Preconditioning-regulated Autophagy Assists Cardiopmentioning
confidence: 99%